Porang Cultivation Techniques for Improving the Welfare of the Sipahutar Village Community 1 - Owen De Pinto Simanjuntak; Alfi Sapitri; Vivi Asfianti (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2022)
Basically, there are many plants that are efficacious and have economic value, one of which is porang.Amorphophallus muelleri Blume is a type of porang that grows in Indonesia and has high economic value because the tubers contain glucomannan. Glucomannan is useful in food, health, cosmetics, and other industries. The benefits of glucomannan in health are lowering cholesterol levels, normalizing triglyceride levels in the blood, controlling blood sugar levels, and improving intestinal performance. The purpose of this activity is the use of porang as a companion plant that is cultivated to increase economic income in Sipahutar I Village, Sipahutar District, North Tapanuli Regency. The stages of the research method are 1) tissue culture techniques to obtain porang seedlings en masse, including making subcultures, maintaining culture results, and observing culture results; 2) Focus Group Discussion (FGD) method in the form of outreach and training on porang cultivation, production, maintenance, and marketing (digital marketing).